Soul of the elephant [videorecording (DVD)] - Joubert, Dereck (PBS Distribution, 2015)
Ironically, every dead elephant with its ivory intact is a reason to celebrate. It means an elephant died of natural causes, and a soul was celebrated and mourned by its herd. Award-winning filmmakers Dereck and Beverly Joubert start with the remains of two bull elephants and through a series of key flashbacks, look at the lives they would have led.